A study of Immune Response in Cyprinus carpio Infected with Aeromonas hydrophila and Treated by Alhagi maoururum Powder. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research was conducted to estimate the immune response of cyprinuscarpio fishes which are infected with A.hydrophila and treated by Alhagi root powder, for this reason atotal number of 60 fishes were used, those fishes were allotted on 6 treatments, The 1st treatment was given 2.5% of Alhagi root powder, The 2nd treatment was given 3.0% , The 3rdtreatment was given 3.5% Alhagi root powder. Mean while the 4thtreatment was given a control diet with out any supplement but fishes in this treatment were injected by A..hydrophila vaccine, the 5thtreatment was given a control diet and injected by the normal saline. Moreover the the 6th treatment was considered as a control treatment and fed on the control diet. Results showed a significant surpassing (p